From wristbands to implants: the transformative role of wearables in heart failure care - Gregório, Catarina (2024)
© 2024 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).